Chemoselective condensationof beta-naphthol, dimethyl malonate, andaromatic aldehydes promoted by niobium pentachloride - Bartolomeu, Aloisio de Andrade [UNESP]; Menezes, Manoel Lima de [UNESP]; Silva-Filho, Luiz Carlos da [UNESP] (Taylor &francis Inc, 2015)
A multicomponent reaction of β-naphthol, dimethyl malonate, and aromatic aldehydes in the presence of NbCl5 as promoter is described. Under similar conditions, aromatic aldehydes with different substituents exhibited different behaviors than β-naphthol and dimethyl malonate. In these MCRs, 4-aryl-3,4-dihydrobenzo[f]coumarins are obtained as the major products (41–93%) and 14-aryl-14H-dibenzo[a,j]xanthenes as the minor products (1–38%).
Keywords: Chemoselective; Niobium pentachloride; Multicomponent reactions; Lewis acid; 4-Aryl-3; 4 dihydrobenzo[f]coumarins; 4-Aryl-3,4-dihydrobenzo[f]coumarins